Detection of stain formation on teeth by oral antiseptic solution using fiber optic displacement sensor - Rahman, H.A.; Rahim, H.R.A.; Harun, Sulaiman Wadi; Yasin, M.; Apsari, R.; Ahmad, Harith; Wan Abas, Wan Abu Bakar (Elsevier, 2013)
The application of a simple intensity modulated fiber optic displacement sensor for the detection of stain formation on human teeth is demonstrated. The proposed sensor uses a concentric type bundled plastic optical fiber (POF) as a probe in conjunction with the surfaces of five human teeth as the reflecting targets. Prior to the experiment, the stains were produced extrinsically by soaking the teeth in different concentrations of oral antiseptic solution containing hexetidine. The concentration of the oral antiseptic solution is measured in volume. For a concentration change from 0 to 80, the peak voltage decreases exponentially from 1.15 mV to 0.41 mV with a measured resolution of 0.48 and 1.75 for concentration ranges of 0-40 and 40-80, respectively. The correlation between the detector output and variation in the color of human tooth surface has successfully been examined. Simple in design and low in cost, this sensor can detect color changes due to hexetidine-induced stain on a tooth surface in a fast and convenient way. Thus, this sensor will be very promising in esthetic dentistry, dental color matching techniques, chemical and biomedical applications. Â© 2012 Elsevier Ltd.